Remdesivir and the Liver: A Concise Narrative Review of Remdesivir-Associated Hepatotoxicity in Patients Hospitalized Due to COVID-19 - Alireza FakhriRavari; Mazyar Malakouti (MDPI AG, 2024)
Severe acute respiratory syndrome coronavirus 2 has infected millions of people, but about 20% of infected individuals do not develop symptoms. COVID-19 is an inflammatory disease that affects a portion of individuals infected with the virus and it is associated with liver injury and other complications, leading to hospitalization, critical illness, and death. Remdesivir is an antiviral agent used for the treatment of hospitalized patients with COVID-19 to improve the time to recovery, reduce the duration of mechanical ventilation, decrease the need for supplemental oxygen, and decrease the risk of mortality. Remdesivir-associated hepatotoxicity has been observed as increased transaminases more than five times the upper limit of normal in hospitalized patients with COVID-19, but causality has not been proven. It is generally difficult to distinguish between remdesivir-associated hepatotoxicity and COVID-19-induced hepatotoxicity. The purpose of this review is to evaluate the evidence for remdesivir-associated hepatotoxicity. Current evidence suggests that elevated liver enzymes in hospitalized COVID-19 patients are more likely to be due to the infection than remdesivir, and a 5-day course of remdesivir seems to be safe in regard to hepatotoxicity.